2022
DOI: 10.1364/oe.473075
|View full text |Cite
|
Sign up to set email alerts
|

Capability and convergence of linearized invariant-imbedding T-matrix and physical-geometric optics methods for light scattering

Abstract: The linearized invariant-imbedding T-matrix method (LIITM) and linearized physical-geometric optics method (LPGOM) were applied on regular hexagonal prisms from small to large sizes to obtain the scattering properties and their partial derivatives. T-matrices and their derivatives from the LIITM are presented and discussed in the expansion order, where the minor diagonal elements are dominant. The simulation results of single-scattering properties and their corresponding linearization from both methods are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The aforementioned algorithms, such as IITM, EBCM, and PGOM, have been linearized and validated by the finite difference method and against each other [51][52][53][54]. Previous studies have shown that single scattering properties calculated by the linearized IITM and PGOM (abbreviated as LIITM and LPGOM) are sufficiently accurate for a wide range of size parameters [55]. To reduce the burden of computation and time for the finite difference approximation of the retrieval, a linearized single scattering property database was pre-calculated in this study by employing a combination of LIITM and LPGOM.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned algorithms, such as IITM, EBCM, and PGOM, have been linearized and validated by the finite difference method and against each other [51][52][53][54]. Previous studies have shown that single scattering properties calculated by the linearized IITM and PGOM (abbreviated as LIITM and LPGOM) are sufficiently accurate for a wide range of size parameters [55]. To reduce the burden of computation and time for the finite difference approximation of the retrieval, a linearized single scattering property database was pre-calculated in this study by employing a combination of LIITM and LPGOM.…”
Section: Introductionmentioning
confidence: 99%